2015
DOI: 10.1111/all.12640
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping asthma, rhinitis and eczema in MeDALL population‐based birth cohorts: an allergic comorbidity cluster

Abstract: Phenotyping asthma, rhinitis and eczema in MeDALL population-based birth cohorts: an allergic comorbidity cluster. Allergy 2015; 70: 973-984. AbstractBackground: Asthma, rhinitis and eczema often co-occur in children, but their interrelationships at the population level have been poorly addressed. We assessed co-occurrence of childhood asthma, rhinitis and eczema using unsupervised statistical techniques. Methods: We included 17 209 children at 4 years and 14 585 at 8 years from seven European population-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
83
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 46 publications
11
83
0
4
Order By: Relevance
“…In all the studies, infants were considered as 'high risk' if they had one or more family members with eczema, asthma, gastrointestinal allergy, allergic urticaria or allergic rhinoconjunctivitis. Atopic dermatitis and eczema were diagnosed and defined as a pruritic, chronic or chronically relapsing noninfectious dermatitis with typical features and distribution (34). Clinical diagnosis of asthma, wheezing and rhinoconjunctivitis was made according to international guidelines.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…In all the studies, infants were considered as 'high risk' if they had one or more family members with eczema, asthma, gastrointestinal allergy, allergic urticaria or allergic rhinoconjunctivitis. Atopic dermatitis and eczema were diagnosed and defined as a pruritic, chronic or chronically relapsing noninfectious dermatitis with typical features and distribution (34). Clinical diagnosis of asthma, wheezing and rhinoconjunctivitis was made according to international guidelines.…”
Section: Literature Searchmentioning
confidence: 99%
“…Wheeze was defined as an episode with obstructive airway symptoms. Asthma was defined as a chronic inflammatory disorder of the airways, usually associated with airway hyper-responsiveness and variable airflow obstruction, that is often reversible spontaneously or under treatment (34)(35)(36), needed to be doctor diagnosed through clinical symptoms and/or medication during the last 12 months and/or wheeze or nocturnal cough and a positive reversibility test and/or pathological Fraction of Exhaled Nitric Oxide (FENO) value. Asthma is often associated with rhinitis, an inflammation of the nasal mucosa and/or conjunctivitis, an inflammation of the conjunctiva (37).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Children, in particular, frequently present concomitant or consecutive diseases [2,3], something that we refer to as allergic multimorbidity. The MeDALL (Mechanisms of the Development of Allergy) study [4], including both canonical epidemiological methods [5] and unsupervised cluster analysis [6], has shown that coexistence of asthma, eczema and rhinitis in the same child is more common than expected by chance alone, supporting the existence of a multimorbidity cluster. Although IgE sensitization is independently associated with excess multimorbidity of asthma, eczema and rhinitis, its presence accounted only for 38% of multimorbidity [5], suggesting that both IgE and non-IgE mechanisms are involved in the multimorbidity of these diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In children with asthma, co-occurrence with rhinitis and/or atopic dermatitis has been reported to be as high as ∼44% 16. There is mixed evidence of the nature of the relationship between asthma and allergic conditions, with evidence of both a causal relationship17 18 and common causes,19 including subsets of genes 20…”
Section: Introductionmentioning
confidence: 99%